2012
DOI: 10.1002/pola.26253
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the mechanism of surface‐initiated atom transfer radical polymerization from a diazonium‐based initiator layer

Abstract: This study elucidates the influence of the atom transfer radical polymerization initiator structure, monolayer versus disordered multilayer, on the growth kinetics and the structural transition of poly(methyl methacrylate) (PMMA) brush layers. The multilayer initiator film, prepared by acylation of the electrografted 2‐phenylethanol layer using 2‐bromoisobutyryl bromide, consists of ∼4.6 times more tert‐butyl bromide groups compared to monolayer initiator prepared by self assembly technique. The results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In contrast, using the enriched GCBnBr* film, the results were much more encouraging in that polymer brushes of ∼15 nm thickness became available. These results are in line with a previous study , showing the importance of having a high initiator density to enable the formation of stretched brush structures. For the GCBnBr* an increase in the oxygen was seen during the Wohl‐Ziegler bromination, which may arise from reaction of the benzylic radical with trace amounts of oxygen forming hydroxyl groups.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, using the enriched GCBnBr* film, the results were much more encouraging in that polymer brushes of ∼15 nm thickness became available. These results are in line with a previous study , showing the importance of having a high initiator density to enable the formation of stretched brush structures. For the GCBnBr* an increase in the oxygen was seen during the Wohl‐Ziegler bromination, which may arise from reaction of the benzylic radical with trace amounts of oxygen forming hydroxyl groups.…”
Section: Resultssupporting
confidence: 93%
“…In the case of X=CH 2 Br the organic films are of particular interest, having served as radical initiators in ATRP processes to generate surface‐attached polymer brushes . Both the density and thickness of the polymer brush films are to a high extent determined by the bromine density . Here, it is shown that the bromine abstraction reaction lowers the quality of the initiator film significantly but, also, that the film can be repaired by enriching its content of bromine using a Wohl‐Ziegler bromination prior to the ATRP.…”
Section: Introductionmentioning
confidence: 88%
“…The dry state thicknesses of the PMMA layer on Ni‐Gra‐PMMA Y is on average 10.1 ± 1.0 nm (corrected for the thickness of the initiator films and including both batches) with a tendency of a slight increase going from Y = 1 to 5. Surprisingly, the increase in atomic concentration of Br for batch #1 from 1.8% for Ni‐Gra‐Br 1 to 3.0% for Ni‐Gra‐Br 5 recorded in XPS is not reflected in the formation of a substantially thicker polymer film, which, otherwise, is seen in the case of glassy carbon[23a] and gold substrates. However, the relatively high uncertainty associated with the ellipsometry measurements may simply be the cause of this discrepancy.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time the expected correlation between the bromine and brush contents for Ni‐Gra‐Br Y and Ni‐Gra‐PMMA Y , respectively, would then ensue in accordance with our previous studies on the growth of PMMA brushes on glassy carbon and gold. [23a,]…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have chosen to prepare initiator-modified surfaces by a two-step procedure including first the electrochemical reduction of aryl diazonium salts to produce active layers and second the post-functionalization of the modified substrate with the initiator. In most cases, 4-(2-hydroxyethyl) benzene diazonium, synthetized from the corresponding commercial aniline precursor, is used to prepare a reactive platform with hydroxyethyl functionalities inducing addition-elimination reaction on an acyl bromide (bromopropionyl bromide 182 or 2-bromoisobutyryl bromide [218][219][220][221] ). The second postfunctionalization option considered is based on the formation of a carboxyphenyl platform on which the initiator is immobilized via a one-step 222 or a three-step 90 procedure.…”
Section: Polymer Growthmentioning
confidence: 99%